The Rise in the Disability Rolls and the Decline in Unemployment - Autor, D. H.; Duggan, M. G. (Quarterly Journal of Economics, 2003)
Between 1984 and 2001, the share of nonelderly adults receiving Social Security Disability Insurance income (DI) rose by 60 percent to 5.3 million beneficiaries. Rapid program growth despite improving aggregate health appears to be explained by reduced screening stringency, declining demand for less skilled workers, and an unforeseen increase in the earnings replacement rate. We estimate that the sum of these forces doubled the labor force exit propensity of displaced high school dropouts after 1984, lowering measured U. S. unemployment by one-half a percentage point. Steady state calculations augur a further 40 percent increase in the rate of DI receipt.